Microalbuminuria as a marker of kidney damage in patients with arterial hypertension - Yanet Herrera Calderón; María de Lourdes Menéndez Villa; Miguel Angel Serra Valdes (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Arterial hypertension is a powerful risk factor for kidney damage. The prevalence is very high among patients with chronic kidney disease. Objective: To determine the presence of microalbuminuria as a marker of kidney damage in patients with arterial hypertension admitted between September 2016 and September 2017. Material and Methods: A descriptive, longitudinal, prospective study was conducted in 123 patients. Age; sex; cholesterol, triglycerides, creatinine and microalbuminuria levels and vascular risk factors were determined. Descriptive and inferential statistics were used. Results: The 40.7% of patients belong to the group of patients of age more than 70 years, predominating the male sex (65%); 62.6% of them presented microalbuminuria and 97.3% had risk factors associated with an increased prevalence of smoking, dyslipidemia, obesity, and vascular diseases associated with RP> 1. The group of patients older than 70 years, male, and with presence of microalbuminuria predominated in the study. The presence of more than three risk factors was associated with microalbuminuria. The presence of microalbuminuria increased with the years of evolution of the disease. Stage 3 of chronic kidney disease predominated in patients with arterial hypertension and microalbuminuria and it was directly related to the years of evolution of arterial hypertension. Conclusions: The determination of microalbuminuria in patients with arterial hypertension is a simple and important risk marker to determine subclinical kidney damage and it is closely related to the increase in the age of the patient, the years of hypertension, and the association with other risk factors for vascular disease. Keywords: Arterial hypertension, microalbuminuria, risk factors, chronic kidney disease.